1991
DOI: 10.1093/jac/27.suppl_a.117
|View full text |Cite
|
Sign up to set email alerts
|

A comparative safety and efficacy study of clarithromycin and erythromycin stearate in community-acquired pneumonia

Abstract: The efficacy and tolerance of clarithromycin and erythromycin stearate in the treatment of community-acquired pneumonia were compared in a multicentre, double-blind randomized trial. Two hundred and eight adult patients were randomized to receive either clarithromycin 250 mg 12-hourly (96 patients) or erythromycin stearate 500 mg 6-hourly (112 patients), each for 14 days. One hundred and eight patients were evaluable for efficacy, 64 receiving clarithromycin and 44 erythromycin stearate. There was no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…The mITT clinical cure rate of 85.9% (171/199) for telithromycin compares favorably with those reported for other antimicrobial agents currently available for the treatment of CAP [31][32][33][34][35][36]. Furthermore, the findings of the present study are particularly encouraging in light of the study design, and have since been confirmed in three further clinical trials of the efficacy of telithromycin in CAP, two of which included clarithromycin and trovafloxacin, respectively, as comparator agents [37][38][39].…”
Section: Discussionsupporting
confidence: 63%
“…The mITT clinical cure rate of 85.9% (171/199) for telithromycin compares favorably with those reported for other antimicrobial agents currently available for the treatment of CAP [31][32][33][34][35][36]. Furthermore, the findings of the present study are particularly encouraging in light of the study design, and have since been confirmed in three further clinical trials of the efficacy of telithromycin in CAP, two of which included clarithromycin and trovafloxacin, respectively, as comparator agents [37][38][39].…”
Section: Discussionsupporting
confidence: 63%
“…A significantly higher clinical cure rate for clarithromycin compared to erythromycin stearate has been reported in communityacquired pneumonia (CAP), with a lower rate of adverse effects in the clarithromycin group [32]. A high clinical cure rate for clarithromycin used in acute bacterial exacerbations of chronic bronchitis has also been reported [33].…”
Section: Discussionmentioning
confidence: 99%
“…This situation appears to be analogous in many ways to that for genital infection with C. trachomatis; no one would even consider evaluating antimicrobial efficacy by serology. However, the only treatment studies of pneumonia caused by C. pneumoniae that have been published in journals so far have relied entirely on diagnosis by serology (1,37).…”
Section: Susceptibility Testing Of C Pneumoniaementioning
confidence: 99%